Repetitive Control With Adaptive Sampling Frequency for Wind Power Generation Systems - Herrán, Mario Alejandro (2014)
This paper presents a novel repetitive control (RC) for wind power generation systems (WPGS), which achieves optimal performance in steady-state conditions due to a variable sampling/switching period technique (VSPT). The main objective of VSPT is to obtain an integer number of samples per grid period, which solves the main problem of RC, i.e., the loss of rejection to periodic disturbances due to grid frequency drift. The sampling/switching frequency is adjusted with a variable sampling period filter phase-locked loop, which also adds robustness to the system due to its inherent tolerance to grid voltage distortion and unbalances, and events such as frequency steps and faults. The control and synchronism subsystems are described, designed, and verified experimentally in a 10-kW WPGS. The results obtained prove the accuracy of the proposed control even under severe disturbances, typical in grids with high WPGS penetration, providing ancillary functions to enhance reliability and reduce operational costs.